Management of Pediatric Displaced Distal Metaphyseal Forearm Fracture: Comparison between Cast Immobilization and Percutaneous Kirschner Wire Fixation - Shrestha, D; Dhoju, D; Parajuli, N; Dhakal, G; Shrestha, R (Nepal Orthopaedic Association Journal, 2013)
Background: Distal metaphyseal forearm fracture is one of the common injuries in children. Closed reduction and above elbow cast is the standard method of treatment but reported to be associated with redisplacement rate of 7-25%. Closed reduction and fixation with percutaneous Kirschner wire is an alternative treatment option to prevent redisplacement. Methods: Thirty five children (group I) of age between 6 to 13 yrs with displaced ( more than 50% of cortical diameter) or angulated (more than 20°) distal metaphyseal forearm fracture managed with closed reduction and above elbow cast were compared with 21 children (group II) managed with closed reduction and percutaneous crossed Kirschner fixation. Clinical outcomes and complications were compared in both groups after 12 weeks of follow up. Results: Preoperative variables in both the groups were comparable. Mean loss of elbow flexion and extension (12° vs. 4°, p =0.08), wrist dorsflexion and palmerflexion (27° vs. 14°, p=0.12) and forearm supination and pronation (27° vs. 15°, p= 0.143) were more in group I but were statistically not significant. Complications rate (28.4% vs. 19.04%, p= 0.04) was higher in group I (such as fracture redisplacement and swelling) than in group II (pin tract infection). Conclusions: Grossly displaced or angulated distal metaphyseal forearm both bone fracture in children treated with either closed reduction and above elbow cast or closed reduction with crossed Kirschner wire fixation have no statistically significant clinical outcomes in terms of loss of movement of elbow, wrist and forearm but complication rate is higher in cast group. Percutaneous Kirschner wire fixation prevents redisplacement. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8133 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 1-6